2012
DOI: 10.1039/c2dt12497a
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescence “turn-on” chemodosimeter for Cu2+ in aqueous solution based on the ion promoted oxidation

Abstract: We developed a novel method for Cu(2+) detection based on the ion promoted oxidation reaction. Chemodosimeter L (weak fluorescence) can be oxidized into 3-benzothiazoly-7-N,N-diethylaminocoumarin (strong green fluorescence, coumarin 6) by Cu(2+) with high selectivity and sensitivity in HEPES (10 mM, pH = 7.4) buffer containing 50% (v/v) water-CH(3)CN solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…On the other hand, Cu 2+ is not only a significant metallic pollutant, but also an essential element for living organisms. [3][4][5][6] So far, many progress has been achieved in the creation of a chemosensor for Cu 2+ , [7][8][9][10][11][12][13][14][15][16][17][18] however there is still room to develop easy-to-make, simple-to-use and observable colorimetric sensors for Cu 2+ in aqueous solution. Work related to this area is of great challenge and increasing interest.…”
mentioning
confidence: 99%
“…On the other hand, Cu 2+ is not only a significant metallic pollutant, but also an essential element for living organisms. [3][4][5][6] So far, many progress has been achieved in the creation of a chemosensor for Cu 2+ , [7][8][9][10][11][12][13][14][15][16][17][18] however there is still room to develop easy-to-make, simple-to-use and observable colorimetric sensors for Cu 2+ in aqueous solution. Work related to this area is of great challenge and increasing interest.…”
mentioning
confidence: 99%
“…Sb was determined from the emission intensity of the sensor solution in the absence of metal ions by performing a series of five measurements. The detection limit was calculated from the calibration plot and the values are collected in Table 3 [72,73]. The detection limit for complexes 1-4 was found to be in the range of 1.2 × 10 -6 -4.3 × 10 -6 M. The detection limit for complex 1 (4.3 × 10 -6 M) was higher compared to complex 4 (1.2 × 10 -6 M),…”
Section: Luminescence Spectral Titrationmentioning
confidence: 99%
“…Upon addition of Zn 2+ , the proton peak of the -CO-NH at 12.12 ppm disappeared. This was possible because addition of Zn 2+ to HL caused the enolization of -CO-NH (COH_N) [47] and the loss of the -OH proton with subsequent binding to electron deficient Zn 2+ , the signals (8,9) were shifted to low-field compared to that in the 1 HNMR spectrum of the parent ligand HL which were attributed to the binding mode of Zn 2+ and the oxygen of -COO and the nitrogen atom of the -C_N, in addition, the aryl protons also have different changes in chemical shift. Therefore, the large differences of the 1 H NMR spectra of HL in the absence and presence of Zn 2+ , coupled with ESI-MS and Job's plot analysis, suggested that HL chelated Zn 2+ through interactions with the oxygen of -COO, the nitrogen atom of the -C_N and oxygen of the COH_N and forms 1:1 complex.…”
Section: H Nmr Titrationmentioning
confidence: 99%
“…They play some critical roles in a variety of biological process such as gene transcription, regulation of metalloenzymes, and neural signal transmission in the human body [4][5][6][7][8]. Hence, a quantity of Zn 2+ and Cu 2+ is essential and beneficial for our good health.…”
Section: Introductionmentioning
confidence: 99%